Catalyzing the global energy transition through regions and finance - Ana Camelo Vega (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
The global energy transition, essential for achieving climate goals and sustainable development, faces significant challenges, particularly in emerging markets and developing economies. These challenges include high capital costs, policy inconsistencies, debt burdens, and limited mobilization of private capital due to high perceived risks. This paper explores the importance of regional perspectives in overcoming these barriers, emphasizing how regional public goods, cross-border investments, and tailored financial mechanisms can drive scalable solutions. It provides a comprehensive assessment of regional contexts- highlighting opportunities and constraints in Africa, Asia and the Pacific, and Latin America and the Caribbean-and identifies the potential of innovative financial catalysts, namely blended finance. The analysis underscores the critical role of regional collaboration and financial innovation in fulfilling global commitments, such as the latest USD 300 billion pledge, and presents actionable recommendations for policymakers, international financial institutions, and private sector stakeholders to accelerate the energy transition equitably and effectively.
Keywords: Q01; Q40; F35; G23; O16; 330; Sustainable Finance; Energy Transition; Cost of Capital; Emerging Markets; Regional Pathways